2004
DOI: 10.1017/s095283690400528x
|View full text |Cite
|
Sign up to set email alerts
|

River dolphins and flooded forest: seasonal habitat use and sexual segregation of botos (Inia geoffrensis) in an extreme cetacean environment

Abstract: Habitat use by the boto, or Amazon river dolphin Inia geoffrensis, was investigated in and around the Mamirauá Reserve, Brazil. Largely forested with numerous channels and lakes, Mamirauá comprises a variety of seasonal floodplain habitats known collectively as várzea. The annual cycle of flooding in this region (amplitude 11-15 m) dominates all life. Profound seasonal differences in dolphin density between habitats were consistent with known fish movements, in turn dictated by changes in water level and disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
117
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 19 publications
10
117
2
5
Order By: Relevance
“…This result is most likely a consequence of dolphins (1) travelling into tributaries and being temporarily unavailable for sampling, (2) hiding amongst debris, or (3) failing to surface within sight of the observation crew. Similar behavior has been shown to occur in the botos of the Amazon, where sexual segregation occurs during seasonal floods (McGuire & Winemiller 1998, Martin & da Silva 2004. Our methodology provides a standardized protocol, and should be applied to future surveys monitoring the status of the Critically Endangered Nepalese dolphin population.…”
Section: Discussionsupporting
confidence: 58%
“…This result is most likely a consequence of dolphins (1) travelling into tributaries and being temporarily unavailable for sampling, (2) hiding amongst debris, or (3) failing to surface within sight of the observation crew. Similar behavior has been shown to occur in the botos of the Amazon, where sexual segregation occurs during seasonal floods (McGuire & Winemiller 1998, Martin & da Silva 2004. Our methodology provides a standardized protocol, and should be applied to future surveys monitoring the status of the Critically Endangered Nepalese dolphin population.…”
Section: Discussionsupporting
confidence: 58%
“…Our model results indicated that more Sotalia were seen at earlier hours of the day and during the dry season. Our results are similar to those obtained from previous work in areas where dolphin densities were observed as highest when river levels were at their lowest (AliagaRossel, 2002;Martin & Da Silva, 2004b;Kelkar et al, 2010). This variation in dolphin density can be attributed to seasonal movements, as individuals that prefer to inhabit tributaries have to move to areas that do not dry out (Martin & Da Silva, 2004b).…”
Section: Discussionsupporting
confidence: 91%
“…Bolivia and Peru had the highest overall densities, and confluences and lakes were highlighted in terms of habitat preferences (Gómez-Salazar et al, 2012). These areas have previously been reported as abundance hot spots for both species (Martin et al, 2004;Martin & da Silva, 2004b;Mcguire & Aliaga-Rossel, 2014).…”
Section: ____________________ Corresponding Editor: Enrique Cresposupporting
confidence: 57%
See 2 more Smart Citations